Vulnerability to heat exposure: Spatial variations and the role of demographic and socioeconomic status in Florida - Xiuling Zhao; Bertram Melix; David Hsu; Emily Powell; Emily W. Harville; Jessica A. Broach; Christopher K. Uejio (Sustainable Cities and Society, 2026)

Multi-objective optimization of biological nitrogen removal process in industrial wastewater based on GPS-X simulation and entropy-weighted TOPSIS - Shishan Zhou; Yongchao Zhao; Jiangli Lin; Shuailian Zhao; Xiaojing Yao; Xiuling Zhu; Xiangyun Wei; Zhen Su (Journal of Water Process Engineering, 2026)

Corrigendum to “PMs-Ti4+-based plasma extracellular vesicles glycoproteomics and its application in lung cancer” [Anal. Chim. Acta 1405 (2026) 345449] - Xinxin Zheng; Fangfang Xiong; Yanyan Zhao; Xiuling Li; Zhiyu Liu; Xinmiao Liang (Analytica Chimica Acta, 2026)

PMs-Ti4+-based plasma extracellular vesicles glycoproteomics and its application in lung cancer - Xinxin Zheng; Fangfang Xiong; Yanyan Zhao; Xiuling Li; Zhiyu Liu; Xinmiao Liang (Analytica Chimica Acta, 2026)

Optimizing hydrogenation activation pathway in Cu-based hierarchical microspheres for sustainable nitrophenols hydrogenation with ultralow-reductant-consumption - Fengting Geng; Jiajia Cheng; Xuexin Niu; Xiaoli Wang; Hongxing Wang; Chaoyue Zhao; Ling Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Lifeng Cui; Longlong Geng (Chemical Engineering Journal, 2026)

Coordination chemistry-guided construction of hierarchical lignin-derived porous carbon with dual Lewis acid–base sites for synergistic CO2 capture - Xinxin Niu; Li Bai; Xiuling Xu; Fujun Wang; Shuai Zhu; Yixian Xue; Zhi Liu; Zhao Chen (Chemical Engineering Journal, 2026)

Temperature-dependent effects of lanthanum-modified bentonite on sediment nitrogen removal processes and the underlying microbial mechanisms - Penglong Wang; Jiehua Wang; Pingping Zhang; Zhiqiang Jiao; Xiuling Bai; Zhonghua Zhao; Jinyue Fan; Songwei Zhang; Bing Zhao; Xiubo Ren; Huidian Dou; Wenhao Bai (Water Research, 2026)

Integrating computational and biological approaches for the discovery of putative MmpL3 inhibitors against Mycobacterium tuberculosis - Likun Zhao; Hongfu Li; Xiuling Ma; Jiahao Sun; Henry H.Y. Tong; Huitao Huang; Hongtou Chan; Xiaojun Yao; Huanxiang Liu; Qianqian Zhang (Molecular Diversity, 2026)

Combined effect of heat and outdoor O3 pollution on emergency department visits in Florida - Xiuling Zhao; Bertram Melix; Emily Powell; Emily W. Harville; Christopher K. Uejio (Environmental Research, 2026)

Span80 induced orderly diffusion of monomer for the construction of small pore volume polyamide nanofiltration membrane with high Li/Mg separation ratio - Lu Gao; Yue Miao; Xiaowen Huo; Yingying Zhao; Zhaojing Jing; Xiuling Liu; Haitao Wang; Ning Fan; Qiuying Jia; Kai Ren; Jun Li; Na Chang (Desalination, 2026)

Hydrogel-confined molecular iron catalyst enables enhanced selective photoelectrochemical oxidation of glycerol to glycolaldehyde - Lu Wang; Zizhong Chen; Qi Zhao; Xiuling Jiao; Dairong Chen; Yuguo Xia (Chemical Engineering Journal, 2026)

Silica Nanoparticles Induce BV-2 Cells Autophagy Via activation of NLRP3 inflammasome and CaMKK2 Signaling Pathways - Tianxiang Liu; Mingqian Wang; Yuanyuan Zhang; Li Yang; Jia Zhang; Hongzhu Wei; Xinyue Li; Huan Pang; Jiali Li; Zhixuan Luo; Mengyue Liu; Haiying Du; et al. (Molecular Neurobiology, 2026)

Biodegradable multifunctional hyaluronic acid hydrogel microneedle band-aids for accelerating skin wound healing - Erman Zhao; Xiuling Tang; Minggao Zhao; Le Yang (Drug Delivery and Translational Research, 2026)

Blocking T-type calcium channels disrupts spermatogenesis in vivo and adversely affects spermatocytes in vitro by impairing mitochondrial function and autophagic flux - Xiuling Zhao; Lei Wang; Shiqin Huang; Lin Liu; Xiaorong Wang; Liping Pu; Hao Chen; Junyu Nie (Reproductive Toxicology, 2025)

Revealing the inhibition mechanism of ultrasound-assisted purified dried apricot polyphenols on α-amylase: Insights from multispectral and computational analyses - Cheng Ma; Zhongyang Li; Jiangli Lin; Bin Wu; Shuailian Zhao; Xiaojing Yao; Xiuling Zhu; Xiangyun Wei; Shishan Zhou (Food Bioscience, 2025)

All-in-one electrochromic windows based on hydrogels containing dual redox pairs for affordable and large-scale applications - Yuling Zhu; Qi Zhao; Chenglong Mu; Yahui Liu; Yuguo Xia; Xiuling Jiao; Dairong Chen; Ting Wang (Chemical Engineering Journal, 2025)

Ether-free PDMS-based composite electrolytes with intrinsic safety, high ionic conductivity and wide electrochemical window for solid state Li-metal batteries - Chenglong Mu; Jinyan Chen; Qi Zhao; Yahui Liu; Yuling Zhu; Zhang Dai; Xina Sui; Xiuling Jiao; Dairong Chen; Ting Wang (Chemical Engineering Journal, 2025)

Combined effects of microplastics and copper on antioxidant capacity, gut microbiome, and metabolomics of Pseudorasbora parva - Baicai Wang; Guoao Xie; Hailun Zhang; Yueting Zhao; Yekai Sun; Hang Yuan; Lijuan Cai; Xiuling Li; Wenxia Wang; Changwei Hu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

pH-regulated structural and interfacial properties of OSA starch/whey protein fiber complexes to improve the storage and digestive stability of citrus essential oil emulsions - Run Ji; Haowen Sun; Zhao Chen; Shuang Song; Hao Guo; Xiuling Zhang; Fei Wu (Carbohydrate Polymers, 2025)

An outcome-wide analysis of maternal air pollution exposure and adverse pregnancy outcomes in intrahepatic cholestasis of pregnancy - Xueqi Li; Xiuling Zhu; Daijuan Chen; Yajie Zhao; Xixi Deng; Yongchi Zhan; Bing Guo; Tingting Xu; Xiaodong Wang (Atmospheric Environment, 2025)

Woody Plant Encroachment Significantly Alters Grassland Soil Microbial Community: A Global Meta‐Analysis - Guoliang Sha; Shuyan Chen; Xuanchen Liu; Wanyu Xia; Hanwen Cui; Anning Zhang; Lizhe An; Zi Yang; Xia Zhao; Jing Zhang; Xiuling Yu; Jing Xiao; et al. (Global Ecology and Biogeography, 2025)
Aim Woody plant encroachment is reshaping grassland ecosystem functions worldwide. While its aboveground impacts are well documented, how this process alters microbial communities—key drivers of belowground processes—remains poorly understood. We aimed to (1) quantify the general effects of global woody plant encroachment on soil microbial community attributes in grasslands and (2) identify the abiotic and biotic factors driving these changes. Location Global grassland ecosystems. Time Period 2000–2024. Major Taxa Studied Soil microbial communities (bacteria, fungi). Methods We conducted a meta‐analysis of 241 paired observations to evaluate changes in microbial composition, diversity, biomass, activity and enzyme activity under woody plant encroachment. Results Woody plant encroachment significantly altered soil properties. Woody plant encroachment also promoted a comprehensive increase in microbial community diversity, biomass, microbial activity and enzyme activity, as well as changes in community composition. The nitrogen‐fixing status of the encroaching species (biotic factor) significantly affected microbial responses: encroachment by nitrogen‐fixing plants resulted in a higher abundance of Bacteroidetes, fungal richness, microbial biomass phosphorus and phosphatase activity compared to non‐nitrogen‐fixing plants. In addition, abiotic factors, such as mean annual temperature, soil organic carbon and total nitrogen were identified as key factors driving microbial responses. Specifically, mean annual precipitation, mean annual temperature and elevation jointly regulated the effects of woody plant encroachment on soil microbial community attributes by influencing plant and soil properties. Main Conclusions This meta‐analysis demonstrated that woody plant encroachment significantly reshaped soil microbial communities in grassland ecosystems. Our findings highlight the role of abiotic factors (climate, elevation, organic carbon and total nitrogen), and biotic factors (nitrogen‐fixing status) in mediating the response of soil microbial communities. These insights contribute to a better understanding of belowground ecological processes and provide valuable guidance for grassland management and predictions of biogeochemical cycles under global change.

Identification of brevis radix (BRX) family genes in tomato (Solanum lycopersicum) and the function of SlBRX5 and SlBRX7 under cold stress - Xiuling Chen; Changhao Mao; Rui Lv; Hecheng Sun; Shusen Liu; Zhao Liu; Aoxue Wang (Plant Science, 2025)

Impact of improved air quality on lung function and blood pressure of middle-aged and older population in China - Xiuling Zhao; Andreas M. Neophytou (Journal of Environmental Sciences, 2025)

Inhibition of recurrence and metastasis in triple-negative breast cancer through nanoparticle-mediated silencing of LPCAT1 to remodel ATP energy metabolism - Xiuling Li; Senlin Li; Haotian Li; Guo Wu; Huijie Zhao; Shaomin Liu; Xiaoding Xu; Phei Er Saw (Science China Life Sciences, 2025)

Functional molecule surface infiltration treatment for efficient all-inorganic perovskite light-emitting diodes - Shurui Chi; Yongjian Chen; Xiuling Li; Jiaqi Wang; Zixun Zhao; Zhuojian Li; Yanqin Miao; Xin Tong; Jinli Liu; Yuechuan Bi; Zongwen Liu; Zhiming Wang; et al. (Chemical Engineering Journal, 2025)

Silica Nanoparticles Induce SH-SY5Y Cells Death Via PARP and Caspase Signaling Pathways - Kai Ma; Tiantian Tian; Xinyue Li; Huan Pang; Xiaofan Ning; Meng Li; Jiali Li; Zhixuan Luo; Tianxiang Liu; Mengyue Liu; Mingqian Wang; Chao Zhao; et al. (Molecular Neurobiology, 2025)

The impact of Span80 single molecule and micelle forms on the structure and performance of polyamide nanofiltration membranes - Yue Miao; Xiaowen Huo; Yingying Zhao; Xiuling Liu; Haitao Wang; Jun Li; Na Chang (Journal of Water Process Engineering, 2025)

Efficient preparation of potassium humate from waste vegetable leaves: Development of a Cu2O@HAK catalyst and innovative application of hydrothermal method - Jiamin Qi; Jiliang Zheng; Yatang Dai; Bo Yang; Haohao Bian; Xinyu Chen; Shunyu Yin; Xiuling Yan; Xiaoyan He; Hongguang Zhao; Yanjie Ren; Changchun Ge; et al. (Journal of Environmental Chemical Engineering, 2025)

Application of composite biological control agent in postharvest preservation of cherry tomatoes - Fanyue Meng; Mozhen Cheng; Ziqi Zhou; Peiwen Wang; Shusen Liu; Zhao Liu; Zhengfeng Song; Xiuling Chen; Aoxue Wang (Physiological and Molecular Plant Pathology, 2025)

Urbanization exacerbates disparities in exposure to air pollution in China - Xiuling Zhao; Weiqi Zhou; Mu Hong; Andreas M. Neophytou (Environmental Research, 2025)

Preparation of calcium-based phosphate adsorbent and mineral-rich humic acid fertilizer from biomass ash and bamboo by hydrothermal-pyrolysis: Performance and mechanism - Xinyue Qiu; Jiliang Zheng; Xiuling Yan; Bekchanov Davronbek; Jose Maria Garcia-Mina; Hao Zhou; Qifeng Zhao; Liyuan Chai; Zhang Lin; Lijuan Zhang; Xintai Su (Environmental Research, 2025)

Long-term pollution status of microplastics in sediment of a typical mariculture area - Xiaodan Wang; Jianmin Zhao; Shuang Zhao; Xiuling Yan; Shuang Guo; Yongliang Liu; Qing Wang; Jianbai Zhang (Marine Pollution Bulletin, 2024)

A Machine Learning Approach for Behavioral Recognition of Stress Levels in Mice - Hao Song; Shirley Shimin Qiu; Binghao Zhao; Xiuling Liu; Yu-Ting Tseng; Liping Wang (Neuroscience Bulletin, 2024)

Analysis of population structure and genetic diversity of Camellia tachangensis in Guizhou based on SNP markers - Dejun Huang; Suzhen Niu; Dingchen Bai; Zhifei Zhao; Caiyun Li; Xiuling Deng; Yihan Wang (Molecular Biology Reports, 2024)
Background Camellia tachangensis F. C. Zhang is a five-compartment species in the ovary of tea group plants, which represents the original germline of early differentiation of some tea group plants. Methods and results In this study, we analyzed single-nucleotide polymorphisms (SNPs) at the genome level, constructed a phylogenetic tree, analyzed the genetic diversity, and further investigated the population structure of 100 C. tachangensis accessions using the genotyping-by-sequencing (GBS) method. A total of 91,959 high-quality SNPs were obtained. Population structure analysis showed that the 100 C. tachangensis accessions clustered into three groups: YQ-1 (Village Group), YQ-2 (Forest Group) and YQ-3 (Transition Group), which was further consistent with the results of phylogenetic analysis and principal component analyses (PCA). In addition, a comparative analysis of the genetic diversity among the three populations (Forest, Village, and Transition Groups) detected the highest genetic diversity in the Transition Group and the highest differentiation between Forest and Village Groups. Conclusions C. tachangensis plants growing in the forest had different genetic backgrounds from those growing in villages. This study provides a basis for the effective protection and utilization of C. tachangensis populations and lays a foundation for future C. tachangensis breeding.

Alkali-assisted hydrothermal preparation of artificial humic acid from litchi wood and electrochemical performance of its hydrochar - Qifeng Zhao; Jiliang Zheng; Xiuling Yan; Davronbek Bekchanov; Liyuan Chai; Zhang Lin; Lijuan Zhang; Xintai Su (Journal of Environmental Chemical Engineering, 2024)

NaCl improves the vegetable quality of Mesembryanthemum crystallinum Linn. by increasing betacyanin and nutrient contents - Yanlu Liu; Qing Liu; Xiuling Liu; Yang Zhao; Yun Liu; Baoshan Wang; Min Chen (Plant and Soil, 2024)

Bismuth oxychloride-sodium alginate hydrogel derived interface desalination solar evaporator for environmental remediation - Xiuling Li; Yangyang Peng; Yanan Pang; Bo Ge; Limin Zhao; Tonghui Zhang; Guina Ren; Zhaozhu Zhang (Chemical Engineering Journal, 2024)

Effect of metal cation crosslinking on the mechanical properties and shrimp freshness monitoring sensitivity of pectin/carboxymethyl cellulose sodium/anthocyanin intelligent films - Run Ji; Xinhua Zhang; Zhao Chen; Shuang Song; Yingying Li; Xiuling Zhang; Wentao Zhang (Carbohydrate Polymers, 2024)

Reducing air pollution does not necessarily reduce related adults' mortality burden: Variations in 177 countries with different economic levels - Xiuling Zhao; Tong Wu; Weiqi Zhou; Lijian Han; Andreas M. Neophytou (Science of The Total Environment, 2024)

Detection and differentiation of seven porcine respiratory pathogens using a multiplex ligation-dependent probe amplification assay - Yingshan Zhou; Haoran Yu; Xiuling Zhao; Jianbo Ni; Shiqi Gan; Wanyu Dong; Jing Du; Xingdong Zhou; Xiaodu Wang; Houhui Song (The Veterinary Journal, 2024)

Rapamycin protects Sertoli cells against BPA-induced autophagy disorders - Junyu Nie; Zhimin Mao; Xuhui Zeng; Xiuling Zhao (Food and Chemical Toxicology, 2024)

Boosting the feasibility of heterogeneous telomerization of 1,3-butadiene with methanol by low-surface-area N-heterocyclic carbene-functionalized hypercrosslinked polymers - Xichao Zhang; Bo Yu; Yuanjun Zhao; Xiuling Guo; Zihao Yang; Xin Ding; Yong Yang (Chemical Engineering Journal, 2024)

Electric field mitigates NH3 and N2O emissions during bioconversion of dairy manure by black soldier fly - Junfang Zhang; Long Chen; Shanshan Zhao; Dejia Hou; Wenjie Qin; Xiuling Zhu; Lei Luo; Deju Chen; Jeffery K. Tomberlin; Zhenyu Zhang; Qing Li (Chemical Engineering Journal, 2024)

Magnetic dendritic mesoporous silica nanoparticles based integrated platform for rapid and efficient analysis of saccharides - Xiuling Zhao; Jiacheng Dong; Yaqian Zhang; Tianrun Wu; Zijun Bie; Yang Chen (Analytica Chimica Acta, 2024)

Influence spatial behavior of surface cracks and prospects for prevention methods in shallow loess tunnels in China - Junling Qiu; Dedi Liu; Kai Zhao; Jinxing Lai; Xiuling Wang; Zhichao Wang; Tong Liu (Tunnelling and Underground Space Technology, 2024)

Effects of extraction methods on the structure and functional properties of soluble dietary fiber from blue honeysuckle (Lonicera caerulea L.) berry - Run Ji; Xiuling Zhang; Chenghai Liu; Wentao Zhang; Xiaofeng Han; Hengtian Zhao (Food Chemistry, 2024)

VDAC1 Protein Regulation of Oxidative Damage and Mitochondrial Dysfunction-Mediated Cytotoxicity by Silica Nanoparticles in SH-SY5Y Cells - Xiaofan Ning; Xinyue Li; Kai Ma; Huan Pang; Tiantian Tian; Huifang Hao; Qiaohong Hou; Meng Li; Tianxiang Liu; Shanshan Hou; Haiying Du; Xiuling Song; et al. (Molecular Neurobiology, 2023)

3D Convolution neural network with multiscale spatial and temporal cues for motor imagery EEG classification - Xiuling Liu; Kaidong Wang; Fengshuang Liu; Wei Zhao; Jing Liu (Cognitive Neurodynamics, 2023)

The Sm gene conferring resistance to gray leaf spot disease encodes an NBS-LRR (nucleotide-binding site-leucine-rich repeat) plant resistance protein in tomato - Huanhuan Yang; Hexuan Wang; Jingbin Jiang; Mingyue Liu; Zengbing Liu; Yinxiao Tan; Tingting Zhao; He Zhang; Xiuling Chen; Jingfu Li; Aoxue Wang; Minmin Du; et al. (Theoretical and Applied Genetics, 2022)

Three Dimensional Statistical Damage Constitutive Model of Rock Based on Griffith Strength Criterion - Song Chen; Xiuling Cao; Zhao Yang (Geotechnical and Geological Engineering, 2021)

Calculation method and statistical characteristics of loosening pressure of a shallow-buried long-span tunnel in composite rock layer with random joint network - Song Chen; Xiuling Cao; Chunsheng Qiao; Zhao Yang; Chaozheng Qiao (Arabian Journal of Geosciences, 2021)

Physiological and RNA-seq analyses provide insights into the response mechanism of the Cf-10-mediated resistance to Cladosporium fulvum infection in tomato - Guan Liu; Junfang Liu; Chunli Zhang; Xiaoqing You; Tingting Zhao; Jingbin Jiang; Xiuling Chen; He Zhang; Huanhuan Yang; Dongye Zhang; Chong Du; Jingfu Li; et al. (Plant Molecular Biology, 2018)

Evaluation of growth and biochemical indicators of Salvinia natans exposed to zinc oxide nanoparticles and zinc accumulation in plants - Changwei Hu; Xu Liu; Xiuling Li; Yongjun Zhao (Environmental Science and Pollution Research, 2014)

Age, trace elements and Hf-isotope composition of zircon in eclogites from the sulu UHP belt, East-Central China: Neoproterozoic intrusion and subsequent Paleozoic and Early Mesozoic metamorphism - Jianping Zheng; Huayun Tang; Junhong Zhao; Yuping Su; Chunmei Yu; Qirong Wei; Qingsheng Liu; Xiuling Wu (Journal of Earth Science, 2010)

Self-Assembled Hydrophobic Honokiol Loaded MPEG-PCL Diblock Copolymer Micelles - MaLing Gou; XiuLing Zheng; Ke Men; Juan Zhang; BiLan Wang; Lei Lv; XiuHong Wang; YinLan Zhao; Feng Luo; LiJuan Chen; Xia Zhao; YuQuan Wei; et al. (Pharmaceutical Research, 2009)

Salt Tolerance is Conferred in Arabidopsis by Overexpression of the Vacuolar Na (+)/H (+) Antiporter Gene SsNHX2, an Alternative Splicing Variant of SsNHX1, from Suaeda salsa - Weihuan Li; Quan Zhang; Xiangqiang Kong; Chunxia Wu; Xiuling Ma; Hui Zhang; Yanxiu Zhao (Journal of Plant Biology, 2009)

Characterization and expression of 42 MADS-box genes in wheat (Triticum aestivum L.) - Tao Zhao; Zhongfu Ni; Yan Dai; Yingyin Yao; Xiuling Nie; Qixin Sun (Molecular Genetics and Genomics, 2006)

A novel cross-linking reagent for bovine hemoglobin modification - Minglei He; Xiuling Lu; Dongxu Zhao; Zhiguo Su (Biotechnology Letters, 2003)